The Proposal for the Allocation of Capacity for International Railway Transport - Zitrický, Vladislav; Černá, Lenka; Abramovič, Borna (Procedia engineering, 2017)
The geographic position of the Slovak Republic and transport flows of goods create assumptions for the development of rail freight transport. Market share of railway transport in the Slovak Republic is about 20% of the overall transport volume. This share is largely formed by the international transport. International railway transport has In the Slovak Republic the significant share of the rail transport performance and therefore it is necessary to find out solutions that improve and strengthen its position. One possibility of development of international railway transport is to set up the conditions for faster transit of trains at cross border stations. The process of border crossing between different rail networks is extensively problematic, not only from the perspective of transfer of transport responsibility for the wagon loads, but also from allocation of the infrastructure capacity for international trains. The opening of rail freight market allows entering of new rail operators to the rail network. To optimise the use of the network and ensure its reliability it is useful to introduce additional procedures to strengthen cooperation on allocation of international train paths for freight trains between infrastructure managers. The paper contains the methodology of the allocation of rail capacity for international railway transport in conditions of Slovak railways. Based on the process transport analysis of cross border stations, common procedure of communication between rail operators and infrastructure manager is designed. Proposed coordination of allocation of the train paths reflects the conditions of common European Union transport market and it provides possibility to increase the competitiveness of railway transport on the transport market.